Retrospective CBCT Evaluation of Missed Root Canals and Their Association with Periapical Lesions in a Makkah-based Population - Alqahtani, Mashael; Mohamed Elsherief, Samia; Afifi, Ibtesam Kamel (UI Scholars Hub, 2026)
Background: Missed root canals are common and can cause persistent periapical disease, making the assessment of their prevalence essential for improving diagnostic accuracy and treatment outcomes. This study aimed to investigate the prevalence of missed canals and evaluate their association with periapical lesions in root canal–treated teeth in the Makkah population. Methods: This retrospective cross-sectional study analysed 815 cone-beam computed tomography scans obtained from Umm Al-Qura University between 2019 and 2024. Missed canals and their association with periapical lesions were assessed by two independent observers. Statistical analysis was performed using the chi-square test. Results: Missed canals were detected in 21% of maxillary and 14.2% of mandibular root canal–treated teeth. A highly significant association was observed among maxillary teeth (p < 0.001), whereas no statistically significant association was found for mandibular teeth (p = 0.25). Periapical lesions were present in 77.9% of maxillary teeth and 69.2% of mandibular teeth with missed canals. Conclusions: Missed canals are common in root canal–treated teeth in the Makkah diverse population and are strongly associated with a high prevalence of periapical lesions. Meticulous canal detection and consideration of population-specific anatomical variations are essential to reduce missed canals, prevent periapical pathology, and enhance endodontic treatment outcomes.